Increasing Literacy on Land Endowment Law for Students of Al-Muhtada Research Islamic Boarding School in Semarang City - Suhadi, Suhadi; Sastroatmodjo, Sudijono; Muhtada, Dani; Isnani, Isnani (Universitas Negeri Semarang, 2022)
Land waqf as a legal institution known in Islamic law has gained a strong position in Indonesian national law based on Law Number 41 of 2014 concerning Waqf. The understanding and practice of land waqf, which has been partly carried out verbally on the basis of mutual trust, has not provided optimal legal certainty and legal protection. In the community, legal literacy is increased in the context of land waqf. Land waqf legal actions that have been carried out based on Islamic law must also be carried out with due regard to national law. The legal act of waqf land must be carried out before the authorized official and registered with the Land Office. The waqf pledge must be made before the registrar of the waqf pledge to be further recorded in the waqf pledge deed. The Waqf Pledge Deed is written evidence in the land registration at the Land Office, as the basis for the issuance of the Waqf Land Certificate. Land Waqf Certificates are issued in order to realize legal certainty and legal protection of land waqf. The regulation of land waqf in the Waqf Law and its implementing regulations further confirms waqf as an important and useful institution for efforts to realize community welfare, in line with the goals of state life.